2004
DOI: 10.5479/si.00775630.529.1
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions within the plantonic food web in mangrove channels of Twin Cays, Belize, Central America

Abstract: The tidal channels of mangrove islands such as Twin Cays, Belize support a productive and diverse microplankton assemblage. In turn, this microplankton community supports large populations of copepods that form dense aggregations in the prop-root environment along the margins of these channels. The growth rate of the phytoplankton community and the grazing rate of the heterotrophic microzooplankton community were measured using the seawater dilution method. In separate experiments, the grazing rate of the swar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In our study, D. oculata presented the highest abundance in October, when low chlorophyll a and pico-and nano-eukaryote values were recorded. These results suggest that D. oculata might feed on other food sources, such as larger protozooplankton, to maintain its large population, as was observed by Buskey et al (2004) when phytoplankton availability is limited.…”
Section: Temporal Variability Of D Oculata and O Davisae In The Southeastern Levantine Seasupporting
confidence: 53%
See 1 more Smart Citation
“…In our study, D. oculata presented the highest abundance in October, when low chlorophyll a and pico-and nano-eukaryote values were recorded. These results suggest that D. oculata might feed on other food sources, such as larger protozooplankton, to maintain its large population, as was observed by Buskey et al (2004) when phytoplankton availability is limited.…”
Section: Temporal Variability Of D Oculata and O Davisae In The Southeastern Levantine Seasupporting
confidence: 53%
“…Santhosh et al (2018) observed that in laboratory conditions, D. oculata feeds on microalgae but can also consume ciliates and similar protozoans. Buskey et al (2004) observed that D. oculata prefers feeding on large cells, showing higher clearance rates when fed on ciliates and autotrophic dinoflagellates compared to heterotrophic dinoflagellates. In our study, D. oculata presented the highest abundance in October, when low chlorophyll a and pico-and nano-eukaryote values were recorded.…”
Section: Temporal Variability Of D Oculata and O Davisae In The Southeastern Levantine Seamentioning
confidence: 94%